IMPROVING STUDENT LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING MODEL IN MATHEMATICS SUBJECT - Yuliani, Dea; Indralin, Vinencia Ika; Maharani, Siti Dewi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
This research aims to enhance the learning outcomes of 3rd grade students at SD Negeri 112 Palembang by applying the problem-based learning model in mathematics on adding fractions with the same denominators. This research uses Classroom Action Research conducted over three cycles: planning, implementation, observation, and reflection. The subjects of this research are 25 students in the 3rd grade class at SD Negeri 112 Palembang. Data collection is carried out through tests and analysis using quantitative data analysis. By applying the problem-based learning model, the research results demonstrate a significant improvement in the students’ learning outcomes regarding the topic of fractions in mathematics. In cycle I, the level of student learning mastery reached 56%; in cycle II, the level of learning mastery increased to 68%; and in cycle III, it reached 84%. In conclusion, applying the problem-based learning model has effectively improved student learning outcomes in mathematics, particularly in fractions material.